Implementation of persuasive design principles in mobile application development: a qualitative study - Nor Afifah Shafin; RD Rohmat Saedudin; Nor Hazana Abdullah (Institute of Advanced Engineering and Science, 2020)
Persuasive design principles (PDP) of persuasive system features framework have shown impressive results from the context of user engagement and acceptance as well as continuous usage towards the persuasive systems involved. Yet, available literatures do not thoroughly address the implementation of these design principles specifically in mobile applications and there is insufficient discussion on the impact of the principles in relation to the overall achievement of mobile applications. Hence, this research was conducted with the aim to qualitatively explore the way PDP were implemented across three different levels of mobile applications’ attainment. For this study, seven semi-structured interviews were conducted with the involvement of fifteen (15) Android mobile applications in the area of utilities category. These mobile applications were then categorized into three categories which is successful, partially successful and less successful based on their numbers of mobile applications downloaded for three consecutive years. The results from the content analysis revealed that each of the PDP were implemented in many ways yet the most common applied principles are reduction, tailoring and personalization. However, the analysis also shows low numbers of implementation from the system credibility and social support category. In addition, most of the mobile applications of the successful category have implemented a lot more PDP as compared to the other two mobile application categories. The results from this study has provide significance towards developers, practitioners as well as the scholars from the contextual perspective of persuasive system framework also the practical values of the principles specifically the implementation in mobile application development.